CAO 2006 Report: Optometric Leaders' Forum - ACO, CAO (Canadian Journal of Optometry, 2021)
CAO held its annual Optometric Leaders' Forum (OLF) in Ottawa, January 27-29. t was a lively and productive session with ample presentations and dialogue surrounding different areas of activity and interest within the optometric community. CAO Committees and Provincial Associations also took this occasion to break out in groups to make presentations and work together to plan for 2006 and beyond.